What Does the Future Hold for Scientific Journals? Visual Abstracts and Other Tools for Communicating Research - Nikolian, Vahagn C.; Ibrahim, Andrew M. (Clinics in Colon and Rectal Surgery, 2017)
Journals fill several important roles within academic medicine, including building knowledge, validating quality of methods, and communicating research. This section provides an overview of these roles and highlights innovative approaches journals have taken to enhance dissemination of research. As journals move away from print formats and embrace web-based content, design-centered thinking will allow for engagement of a larger audience. Examples of recent efforts in this realm are provided, as well as simplified strategies for developing visual abstracts to improve dissemination via social media. Finally, we hone in on principles of learning and education which have driven these advances in multimedia-based communication in scientific research.
Keywords: open access; #VisualAbstract; cognitive theory of learning